Mesthoop doet leven? Stadsmest en een beter bemestingspatroon in de achttiende-eeuwse Vlaamse landbouw - De Graef, Pieter (TSEG - The Low Countries Journal of Social and Economic History, 2017)
Did urban manure nourish the country? Consequences of fertiliser improvement in 18th-century Flemish farming Although traditional societies faced constraints on nutrient availability, the contribution of manuring in general and fertilisation with urban and industrial fertilisers in particular to agricultural growth has hardly been assessed. This article takes the eighteenth-century smallholding economy of the very productive Flemish Husbandry as its starting point and argues on the basis of a micro-level research that both smallholders and larger farmers were prompted to change their fertilisation patterns in the decades after 1750. As a reaction to the economic situation and the landowners’ efforts to nibble at profits by setting higher rents, turning to the use of off-farm fertilisers and intensifying farm production became a compelling strategy for smallholders to safeguard their survival strategies and for larger farmers to retain reasonable profit margins.